2019
DOI: 10.31559/gjeb2019.6.2.8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insurance Sector in the Development of the Economy of Oman

Abstract: Financial mediators carry out the function of directing saving into domestic investment. They simplify effectual distribution of capital resources, which on the other side increase productivity and improve economic effectiveness which leads to decrease capital output ratio. The insurance sector performs exceptionally useful function in economy as financial intermediaries. This paper examined the role of insurance sector in Oman economy using real gross domestic product (GDP) as representative for Oman economy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…He found that there is causality from economic growth to insurance demand, from financial development to economic growth in the short run. Hussein and Alam (2019), who studied the role of the insurance sector in the Oman economy with the data of 2008 -2017, found a positive relationship between growth and the insurance sector. Yenisu (2019) found a negative short term relationship between the insurance premium and economic growth for the period 2010:Q1 -2018:Q4 in Turkey.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…He found that there is causality from economic growth to insurance demand, from financial development to economic growth in the short run. Hussein and Alam (2019), who studied the role of the insurance sector in the Oman economy with the data of 2008 -2017, found a positive relationship between growth and the insurance sector. Yenisu (2019) found a negative short term relationship between the insurance premium and economic growth for the period 2010:Q1 -2018:Q4 in Turkey.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…x) improving credit for the entire society (Hui & Xin, 2017;Hussein & Alam, 2019;Ramoutar, 2019). Besides, Simionescu et al (2017) studying the determinants of economic growth in the Czech Republic, Slovak Republic, Hungary, Poland and Romania have noted that that the FDI promoted economic growth in all countries, except the Slovak Republic.…”
Section: The Impact Of Insurance On Economic Growthmentioning
confidence: 99%
“…It was found out that there was a positive connection between the development of insurance business and economic growth. Hussein and Alam (2019) examined the role which the insurance sector takes in the development of Oman economy between the years 2008-2017. They came out with the result that there was a positive connection between the business of insurance and economic development in Oman for that period of time.…”
Section: Literature Reviewmentioning
confidence: 99%